Determinant factors of fuel consumption behavior: Evidence from Indonesia - PRABUMENANG, A.K.R.; WIBOWO, A.; NARMADITYA, B.S.; PRIHANDONO, D. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The research applied a quantitative explanatory with a descriptive and causal approach. A cluster sampling was engaged in this survey method and collected using structured questionnaires. Furthermore, the data were analyzed undergoing Structural Equation Model (SEM) with the software LISREL 8.8 version. The findings of the study showed that brand image and brand trust do not have an impact on customer satisfaction and repurchase intention of Pertalite. This result implies that customer satisfaction failed in mediating the relationship between brand image and repurchase intention. Besides, customer satisfaction also cannot explain the causality between brand trusts and repurchase intention of Pertalite in Indonesia.RESUMEN La investigación aplicó una explicación cuantitativa con el enfoque descriptivo y causal. Se realizó un muestreo por conglomerados en este método de encuesta y se recopiló mediante cuestionarios estructurados. Además, los datos se analizaron con el modelo de ecuación estructural (SEM) con la versión de software LISREL 8.8. Los resultados del estudio mostraron que la imagen de marca y la confianza de la marca no tienen un impacto en la satisfacción del cliente y la intención de recompra de Pertalite. Este resultado implica que la satisfacción del cliente no logró mediar la relación entre la imagen de marca y la intención de recompra. Además, la satisfacción del cliente tampoco puede explicar la causalidad entre la confianza de la marca y la intención de recompra de Pertalite en Indonesia.